Optimizing photovoltaic efficiency in CZTS solar cells by investigating the role of different advanced materials as back surface field layer - Kamal Zeghdar; Siham Mansouri; Lakhdar Dehimi; Fortunato Pezzimenti; Magda H. Abdellattif; Abdullah M. S. Alhuthali; Chaitany Jayprakash Raorane; R. Balachandran; M. Khalid Hossain (Scientific Reports)
Abstract The fast development of renewable resources requires high-performance and low-cost photovoltaic technologies. CZTS-based solar cells are promising candidates because of the earth-abundant materials and tunable bandgap. However, the efficiencies of these cells are hindered by interfacial recombination. In this study, we numerically analyze the incorporation of back-surface field (BSF) layers to reduce the current losses enhancing the efficiency of a CZTS device. By using systematic SCAPS-1D simulations, we investigated eight different BSF materials (PTAA, Zn3P2, SnS, MoOx, CuI, CNTS, V2O5, and Cu2O) leading us to conclude Cu2O as the one with the highest efficiency, resulting in a record power conversion efficiency (PCE) of 26.19% (~ 110% enhancement with respect to the reference cell performing 12.82%). The precise Cu2O band alignment (CBO: 1.0 eV, VBO: −0.28 eV) is the origin of an effective suppression of carrier recombination while facilitating an effective hole extraction. Promising results in terms of PCE, which remains on the order of 20%, are also achieved for an increased operational temperature of the simulated devices up to 420 K. In addition, further analyses show that the use of V2O5 and CuI as BSF exceeds the conventional design as well (PCE > 24%), when the defect densities are below 10¹⁴ cm-3 and the shunt resistance is > 10⁴Ω·cm². Thus, these studies clearly illustrate whether purposeful BSF integration can surmount fundamental shortcomings of CZTS solar cells, providing a feasible route to viable commercial devices.